New Opportunities for the Humanities: Professional Polylogue in a Multilingual World Review of the first international scientific and practical conference “Professional polylogue in a multilingual world: language, culture, method” (Moscow, April 6–7, 2023) - S. A. Bakaeva; E. A. Samorodova (Дискурс профессиональной коммуникации, 2023)
This paper presents a review of the first International Scientific and Practical Conference “Professional Polylogue in a Multilingual World: Language, Culture, Method”, which was held at MGIMO University (Moscow, Russia) on April 6–7, 2023. The conference aimed to explore various issues related to linguistics, foreign language teaching, and socio-cultural factors in modern language education. The event brought together over 300 specialists who participated as speakers and active listeners in seven sections, three online discussion panels, a round table, and a student section “Potential”. Discussions included significant aspects of foreign language learning, trends and stages in foreign language teaching methods, the formation of professional identity in a multilingual world, and the cultural aspect of learning and self-development of both students and teachers.